Avaliação da dose em pacientes pediátricos submetidos a exame de tomografia computadorizada - Porto, Lorena Elaine (2014)
The computed tomography (CT) dosimetry involves measurements of specific quantities of CT, which are part of CT quality control procedures, as well as calculation of absorbed and effective doses to a patient submitted to CT examinations. Since CT uses ionizing radiation, it should be considered that a precise balance between risks and benefits must be achieved in order to justify the adoption of such technique. Radiation protection of patients undergoing radiological exams is established based on the justification and optimization principles. Nowadays, it is important to know the dose radiation levels to which a patient is exposed during a tomographic procedure. Those are given by the estimation of specific dosimetric quantities called the computed tomography kerma index in air, C100,air, the weighted computed tomography kerma index Cw, kerma length product, PKL,CT and then the levels of effective dose and risk to the computerized CT scan study of skull, thorax and abdomen with a multiple scanning. The values obtained were compared with those obtained by computer simulation using Monte Carlo method. The protection quantities organ absorbed dose, effective dose and risk for comparison with the reference dose level established by the European Community. Using computational simulation program of the Dosecal X_CT and the ICRP 103 Protocol, were certain quantities of radiation protection relevant to study which are the values of effective dose for the procedure. The dose length product PKL,CT level was calculated from the C100,air and compared to the reference dose level established by the European Community. The values found so far are within the limits of the reference levels.